Angiotensin receptor blockade mimics the effect of exercise on recovery after orthopaedic trauma by decreasing pain and improving muscle regeneration. (31st December 2019) - Tawfik, Vivianne L.; Quarta, Marco; Paine, Patrick; Forman, Thomas E.; Pajarinen, Jukka; Takemura, Yoshinori; Goodman, Stuart B.; Rando, Thomas A.; Clark, J. David
Abstract : Key points: Our tibial fracture orthopaedic injury model in mice recapitulates the major manifestations of complex trauma, including nociceptive sensitization, bone fracture, muscle fibrosis and muscle fibre loss. Delayed exercise after complex orthopaedic trauma results in decreased muscle fibrosis and improved pain Losartan, an angiotensin‐receptor blocker with anti‐fibrotic abilities, recapitulates the effect of exercise on post‐injury recovery and may provide an enhanced recovery option for those who are unable to exercise after injury Abstract: Chronic pain and disability after limb injury are major public health problems. Early mobilization after injury improves functional outcomes for patients, although when and how to implement rehabilitation strategies remains a clinical challenge. Additionally, whether the beneficial effects of exercise can be reproduced using pharmacological tools remains unknown and may benefit patients who are unable to exercise as a result of immobilization. We developed a murine model of orthopaedic trauma combining tibia fracture and pin fixation with muscle damage. Behavioural measures included mechanical nociceptive thresholds and distances run on exercise wheels. Bone healing was quantified using microcomputed tomagraphic scanning, and muscle fibre size distribution and fibrosis were followed using immunohistochemistry. We found that the model provided robust mechanical allodynia, fibrosis and a shift to smaller average muscle fibre size lasting up to 5 weeks from injury. We also observed that allowing 'late' (weeks 1–2) rather than 'early' (weeks 0–1) exercise after injury resulted in greater overall running activity and greater reversal of allodynia. In parallel, the late running paradigm was associated with reduced muscle fibrosis, earlier increase in muscle fibre diameter and a short‐term benefit in reducing callus volume. Providing the anti‐fibrotic angiotensin receptor blocker losartan to mice in drinking water reduced both allodynia and muscle fibrosis. Combining losartan and late exercise provided no additional benefit. We conclude that early healing after orthopaedic trauma must be allowed prior to the initiation of exercise to achieve optimal pain, functional and physiological outcomes and that losartan is a viable candidate for translational studies. Key points: Our tibial fracture orthopaedic injury model in mice recapitulates the major manifestations of complex trauma, including nociceptive sensitization, bone fracture, muscle fibrosis and muscle fibre loss. Delayed exercise after complex orthopaedic trauma results in decreased muscle fibrosis and improved pain Losartan, an angiotensin‐receptor blocker with anti‐fibrotic abilities, recapitulates the effect of exercise on post‐injury recovery and may provide an enhanced recovery option for those who are unable to exercise after injury